Memory politics in contemporary Russia : television, cinema and the state (2019)
In the Alexander Gardens in Moscow, next to the Kremlin walls, stands a granite memorial obelisk. It was erected in 1914 to commemorate the 300th anniversary of the Romanov dynasty, but its intended eternal endurance proved short-lived. In 1918, as the Civil War raged across the territory of the former Russian Empire, the obelisk received a makeover. It was refashioned to correspond to the idols of the fledgling socialist state: the Imperial doubleheaded eagle at its crown was removed, and the inscribed names of the Romanov tsars were replaced with those of socialist revolutionaries and philosophers. Then, in 1966, it was relocated to the centre of the gardens to make room for the Tomb of the Unknown Soldier – a symbolic affirmation of the then emerging myth of the Soviet victory in the Second World War. And thus the obelisk stood, as the politically and socially revered idols of the Soviet state ceased to be worshipped and eventually that very state ceased to exist. By then, the names inscribed on the obelisk sounded foreign to the average person’s ear; indeed, many belonged to Western European thinkers and proponents of the socialist cause.1 On the occasion of the 400th anniversary of the Romanov dynasty in 2013 – a manifestly artificial anniversary that was nonetheless extensively marked – the obelisk was restored to its original state.2 On 4 November, the Day of National Unity, the monument was unveiled and blessed by the patriarch of Moscow and All Russia Kirill (Gundiaev). In his speech, the patriarch emphasised the symbolic significance of the restoration for the consolidation of national unity and, by extension, the future existence of the Russian state